2014
DOI: 10.1186/preaccept-1729873135143527
|View full text |Cite
|
Sign up to set email alerts
|

Are anti-HIV IgAs good guys or bad guys?

Abstract: An estimated 90% of all HIV transmissions occur mucosally. Immunoglobulin A (IgA) molecules are important components of mucosal fluids. In a vaccine efficacy study, in which virosomes displaying HIV gp41 antigens protected most rhesus monkeys (RMs) against simian-human immunodeficiency virus (SHIV), protection correlated with vaginal IgA capable of blocking HIV transcytosis in vitro. Furthermore, vaginal IgG exhibiting virus neutralization and/or antibody-dependent cellular cytotoxicity (ADCC) correlated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…[51][52][53] Importantly, no mechanistic evidence has yet been produced showing that dimeric IgAs in complex with virions form large ''aggregates'' that lead to blocking HIV-1 entry at mucosal sites as hypothesized by others. 58 It is possible, however, that through interaction of IgG/IgA with gelforming mucin glycoproteins in vivo, HIV-antibody complexes get trapped in mucus layers, 59,60 and subsequently get washed out by draining, genital secretions. The inefficacy of potent bNAbs in diminishing viral transepithelial migration is on the other hand, contrasting with the blocking capacity on transcytosis that was previously reported for some gp160specific antibodies, especially for IgAs.…”
Section: Discussionmentioning
confidence: 99%
“…[51][52][53] Importantly, no mechanistic evidence has yet been produced showing that dimeric IgAs in complex with virions form large ''aggregates'' that lead to blocking HIV-1 entry at mucosal sites as hypothesized by others. 58 It is possible, however, that through interaction of IgG/IgA with gelforming mucin glycoproteins in vivo, HIV-antibody complexes get trapped in mucus layers, 59,60 and subsequently get washed out by draining, genital secretions. The inefficacy of potent bNAbs in diminishing viral transepithelial migration is on the other hand, contrasting with the blocking capacity on transcytosis that was previously reported for some gp160specific antibodies, especially for IgAs.…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to find an effective anti‐HIV‐1 strategy to impede HIV transmission at the mucosal level (Tudor et al ., 2009). Eliciting an efficient immune response including sIgA or neutralizing IgG to block the viral adherence to the epithelial cells, prevent transcytosis and neutralize the viruses in epithelial cells is the desirable goal of a mucosal vaccine design (Huang et al ., 2005; Zhou and Ruprecht, 2014). Preclinical research showed that passively administered bNAbs can protect macaques from the SHIV challenge even with different relative potency (Pegu et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The high variability of published findings regarding IgA quantitation is likely also influenced by the lack of standardized assays to measure HIV-binding mucosal IgA antibodies and the significant variation in mucosal sampling and purification techniques. [122][123][124] Immunoassays to detect IgA binding to monomeric envelope proteins may not reliably capture functional antibodies targeted to the native HIV virus envelope. Furthermore, lack of antibody HIV-inhibitory activity could indicate that other HIV-independent factors may be involved in host protection.…”
Section: Technical Issues Measuring Anti-hiv Igamentioning
confidence: 99%